Integrating socio-emotional learning into primary education. A leadership-driven approach to fostering holistic student development - Pavlushchenko, Nataliia; Kuznetsova, Oksana; Tolmachova, Iryna; Yeromenko, Olha; Bludova, Yuliia (My University, 2025)
Socio-Emotional Learning (SEL) is an important element of modern education that contributes to the formation of emotional literacy, social skills and academic success of students. The study’s relevance is due to the need to integrate innovative methods to create a favourable educational environment in the face of constant social and psychological challenges. The study aims to investigate the impact of socio-emotional learning programmes on the development of emotional and social competences of primary school students. The research methodology uses quantitative and qualitative approaches, including a quasi-experimental design, questionnaires and semi-structured interviews. The study’s results confirmed the significant positive impact of SES programmes on students’ emotional regulation, social skills and academic performance. The introduction of interactive methods, such as role-playing, integration of SEN into academic subjects, and active parental involvement, helped improve classroom psychological climate and reduce conflict. In particular, students in the experimental group showed significantly higher results in all criteria compared to the control group. The study’s practical significance lies in using the data obtained to develop strategies for the long-term integration of SES programmes into the educational process of primary schools. The results may be helpful for educators, psychologists and curriculum developers.
Keywords: емоційна регуляція; соціальні навички; початкова школа; освітнє середовище; Emotional regulation; Social skills; Primary school; Educational environment